Krysia : a Polish girl's stolen childhood during World War II - Mihulka, Krystyna, 1930-; Goddu, Krystyna Poray (Chicago Review Press, 2017)
The author describes her family's deportation to Russia during World War II and their harsh life working for two years on a remote Soviet collective farm in Kazakhstan before they were allowed to leave and became refugees in Iran.